State of the Young Child in India (Taylor & Francis, 2020)
This Report is one of the first comprehensive studies on young children in India. It focuses on children under 6 years of age and presents key aspects of their well-being and development. It introduces two young child indices aggregating selected indicators to separately track child outcomes and child circumstances and provides an account of the current situation of the young child in terms of physical and cognitive development, access to care, etc. It also explores the policy and legal framework and highlights key recommendations and action points that can help to improve the ecosystem for early childhood care and development.